Implementasi Program Jalan Pintas dalam Pelayanan Administrasi Kependudukan di Dispendukcapil Kabupaten Pasuruan - Mochammad Rendy Eflizar Julian; Agus Widiyarta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Service Network for Persons with Disabilities (Jalan Pintas) program is a program created by the Pasuruan Regency Dispendukcapil because of the direction from the Director General of Dukcapil to create a ball pick-up program movement for persons with disabilities in population administration services. The purpose of this study was to determine the implementation of the Disability Service Network (Jalan Pintas) program in population administration services at the Dispendukcapil of Pasuruan Regency. This research uses descriptive qualitative research with the technique of determining informants through purposive and snowball sampling. The theory used is the implementation theory according to David C. Korten cited by (Christianingrum & Djumiarti, 2019) which has 3 indicators including the suitability of the program to the target group, the suitability of the program to the implementing organization, and the suitability of the target group to the implementing organization. The results showed that the implementation of the Jalan Pintas program in population administration services had gone well. This is evidenced by the dozens of times of picking up the ball which indicates that the Jalan Pintas program is the right program and is needed by people with disabilities. However, on the indicator of the suitability of the target group with the implementing organization, it was found that the Jalan Pintas program was classified as passive because it waited for a report from the village government, community, or Social Services Office so that the program could be implemented.